ANALISIS PENGELOLAAN PASAR TRADISIONAL DALAM MENINGKATKAN EKONOMI MASYARAKAT - Dwi Lasmul Wahyudi; Tarmizi; Muhammad Subham (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This research aims to analyze the management of traditional markets in improving the economy of the Lubuk Ruso Village community and to analyze the Lubuk Ruso traditional market management system from a sharia economic perspective. The method in this research is a descriptive qualitative method. The research objects are market managers and traders at the Lubuk Ruso Traditional Market. Research data sources were obtained through interviews, observation and documentation. The data analysis method used is data collection, data presentation and conclusion drawing. The research results show that the management of the Lubuk Ruso traditional market is considered to be effective where there are core facilities that meet standards based on applicable regulations